Radiographic Assessment of Distomolar Prevalence in Patients Attending to Faculty of Dentistry, University of Benghazi - Areibi, Aisha; Buzaribah, Khadeejah; Eltira, Aziza; Ali, Fowziya (Libyan Journal of Dentistry, 2020)
Background: Extra teeth are usually seen in any area of mandible and maxilla. The distomolar is an extra tooth that occurs in both jaws distal to the third molar, where various studies pointed to assess the occur- rence of distomolars in various people. Objectives: Aimed to estimate the frequency of distomolars in teeth of patient attending to Faculty of Dentistry, University of Benghazi Methods: A total of 3989 panoramic radiographs were examined for patient’s age ranged from 20 years and above. The presences, location and shape of distomolars were studied. There were 1432 women and 2557 men. Results: The outcomes of the study showed that distomolars were detected in 0.18% of the examined people. The extra teeth were noticed in both genders with frequency 0.08% in men and 0.10% in women. In total, 9 extra teeth were detected in 7 patients. Upper jaw distomolars were more frequently observed than lower one. Distomolars in both quadrants of the jaw were found in one female patient and two distomolars were found in another one. All distomolars were impacted. Conclusions: Even though the occurrence of the extra teeth is a little, initial exploration and management are significantly diminish or avoid problems, such as late eruption, non-eruption of teeth, ectopic eruption, abnormal root development or resorption of neighbouring teeth, crowding and cystic lesions.